Crooklyn - Lee, Spike 1957-; Lee, Joie 1962-; Woodard, Alfre 1952-; Lindo, Delroy 1952-; Jafa, Arthur 1960- (Universal, 1999)
Director Spike Lee fashions a bold, flavorful picture of family life in a crowded but cozy Brooklyn neighborhood nicknamed "Crooklyn" by the Carmichaels, who experience one very special summer in their hometown under difficult but often wonderful circumstances
Originally released as a motion picture in 1994
Special Features: Production Notes, Cast & Filmmakers'Bios, Film Highlights, Web Link
Keywords: Families / New York (State) / New York / Drama; African Americans / New York (State) / New York / Drama; Feature films; Films for the hearing impaired; Schwarze. USA; Brooklyn (New York, N.Y.) / Drama; Film; DVD-Video